(untitled) (ModaPalavra e-periódico, 2014)
Critical study of different fashion exhibitions held at major museums in the contemporary world, analyzing their impact on the concepts of fashion and art, as well as the possibilities of fashion exhibitions collaborate in understanding the complex ways of Contemporary Fashion and its relations with the subjects.